Metacognitive Strategies in Learning English:: A Think-Aloud Protocol in Completing Grammar Tasks - Lat, Maria Elena Morales; Yumarnamto, Mateus (Universitas Jambi, Magister Program of English Education Department, 2025)
This study explores metacognitive strategies used by students in learning English grammar. The participants of this study were students of a private university in East Java from three different batches (2020, 2021, and 2022). There were two stages of research conducted: (1) a survey questionnaire and (2) a think-aloud protocol. The survey questionnaire was conducted for all the participants (N=30) using Google Forms. The think-aloud protocol was employed with six selected participants. In the think-aloud stage, the six participants were required to complete a grammar task in the form of sentence combining. While they were working on the task, they said aloud their thought processes. The think-aloud process while they were completing the task was observed and recorded. The questionnaire data were analyzed by means of descriptive statistics, and the transcribed data from the think-aloud protocol were analyzed thematically to find out the metacognitive strategies used in solving the grammar task. The results of this study indicate the usefulness of metacognitive strategies in learning grammar, especially in solving grammar tasks. The findings support previous studies that high achievers in foreign language learning tend to use various metacognitive strategies in their learning.